Increase of the reactivity of a low-active part of lime slurry in soda production - Цейтлін, Мусій Абрамович; Шестопалов, Олексій Валерійович; Райко, Валентина Федорівна (Eastern-European Journal of Enterprise Technologies, 2015)
The study focuses on the reactivity of low-active parts of lime in the solid phase of lime slurry in soda production. It is determined that low-active lime, that is compounds of calcium with oxides of aluminum, iron, silicon and magnesium, is concentrated in fractions with particles over 60 microns in size. It is found that the maximum rate of decomposition of the low-active components of lime is achieved with the increase of its residence time in the reactor to 40-50 minutes at low pH––8-8.5. It is shown that the reactivity of lime milk increases at its dispersion in a vapor-liquid injector due to the cavitational effect. Favorable conditions for the use of low-active parts of lime are possible in recycling the solid unreacted phase in a mixer reactor through a vapor-liquid injector. It is determined that accumulation of the solid recirculating phase in the reactor promotes the removal of supersaturation of the sulfate ion that crystallizes on the surface of the slurry solid particles. The suggested solutions allow both maximizing the use of low-active lime and reducing the reactor operation time to 10 minutes.